2003
DOI: 10.1016/s1097-2765(03)00357-5
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic RNase P

Abstract: Ribonuclease P (RNase P) is an essential enzyme that processes the 5' leader sequence of precursor tRNA. Eubacterial RNase P is an RNA enzyme, while its eukaryotic counterpart acts as catalytic ribonucleoprotein, consisting of RNA and numerous protein subunits. To study the latter form, we reconstitute human RNase P activity, demonstrating that the subunits H1 RNA, Rpp21, and Rpp29 are sufficient for 5' cleavage of precursor tRNA. The reconstituted RNase P precisely delineates its cleavage sites in various sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(39 citation statements)
references
References 44 publications
2
36
0
1
Order By: Relevance
“…M1 RNA may further increase its activity in cultured cells by interacting with cellular proteins (22,31). These properties, as well as the simple design of the guide sequence, make M1GS an attractive and unique gene-targeting agent that can be used generally for basic research and clinical applications.…”
Section: Discussion Engineered Rnase P Ribozyme As a Tool For Studiesmentioning
confidence: 99%
“…M1 RNA may further increase its activity in cultured cells by interacting with cellular proteins (22,31). These properties, as well as the simple design of the guide sequence, make M1GS an attractive and unique gene-targeting agent that can be used generally for basic research and clinical applications.…”
Section: Discussion Engineered Rnase P Ribozyme As a Tool For Studiesmentioning
confidence: 99%
“…Rpp21, Rpp29 and H1 RNA are sufficient for reconstitution of RNase P activity in tRNA processing in vitro (24). The archaeal Rpp21, Rpp29, Pop5, Rpp30 and Rpp38 proteins are required for efficient reconstitution of thermostable RNase P ribonucleoprotein (23,25–27).…”
Section: Nuclear Rnase P: An Ensemble Of Rna With Highly Conserved Prmentioning
confidence: 99%
“…Recent progress in modeling the tertiary folding of eukaryal RNase P RNA uncovers that it has a conserved core structure similar to that of its bacterial counterpart (29). Mutations that disrupt the predicted tertiary folding of H1 RNA abolish catalysis in vitro (24). Remarkably, Kikovska et al, has shown that H1 RNA is active in tRNA processing in vitro in the absence of any protein (30), a finding that is consistent with previous observation that H1 RNA alone binds to precursor tRNAs in vitro and has a conserved catalytic core (24,29).…”
Section: Nuclear Rnase P: An Ensemble Of Rna With Highly Conserved Prmentioning
confidence: 99%
“…Reconstitution using all or some recombinant components has been recently reported for archaeal [Pyrococcus horikoshii (Pho) and Mth] and eukaryal (human) RNase P (22)(23)(24). In these cases, however, the reconstituted RNase P holoenzymes displayed weak activity (compared with either their respective native versions or holoenzymes from other species) and were not fully characterized.…”
mentioning
confidence: 99%
“…It remains to be proven whether the partial (functional) assemblages observed in Pfu RNase P represent common intermediates during hierarchical assembly of archaeal͞eukaryal RNase P holoenzymes. In this regard, it is notable that weak activity was observed when human RPR was reconstituted with human Rpp21 and Rpp29 (24).…”
mentioning
confidence: 99%